Revision total hip arthroplasty using a fluted, tapered, modular stem follow-up method for a mean of three years: A preliminary study - Xing, Shu-Xing; Huang, Qiang; Li, Zheng-Jiang; Li, Yong-Kui; Ban, Zhao-Nan (Frontiers in Physiology, 2023)
Objective: This study aimed to evaluate the results and complications related to revision total hip arthroplasty within a short-to-medium follow up period. Methods: From January 2016 to January 2020, we reviewed 31 prosthetic hip arthroplasty stem revisions using a fluted, tapered modular stem with distal fixation. The median age of the patients was 74.55–79 years. The survival rate was 100%, and there were no re-revisions. The Harris hip score improved from an average of 36.5 ± 7.8 before surgery to 81.8 ± 6.2 at the final follow-up. Results: The average final follow-up was 36 (24–60) months. During this time, there was no periprosthetic infection, no prosthesis loosening or breakage, and no sciatic nerve injury. Complications included four (12.9%) intraoperative fractures and eight (25.8%) dislocations that had no stem fractures. The postoperative limb was lengthened by 17.8 ± 9.8 mm. In most cases, bone regeneration was an early and important finding. Three cases underwent extended trochanteric osteotomy, and bone healing was achieved by the final follow-up. Conclusion: The modular tapered stem reviewed in this study was very versatile, could be used in most femoral revision cases, and allowed for rapid bone reconstruction. However, a long-term follow-up study is needed to confirm these results.